Finansowanie pomocy postpenitencjarnej W latach 2012–2018 - Gumółka, Katarzyna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The subject of considerations encompassed in the article entitled: „Financing post-penitentiary aid” are issues related to obtaining support from the Victims Assistance Fund and Post-penitentiary Assistance (hereinafter: the Fund) by individuals released from prisons and detention centers as well as the impact of the employment of convicts on the income of the above-mentioned Fund. The first part of the article is devoted to the general characteristics of the Fund, including its principles of operations and the time and manner of introducing it into the legal order. The latter part of the article describes the origin of funds dedicated to financing post-penitentiary care, the distribution of funds between individual institutions and which institutions provide post-penitentiary assistance as well as the manner in which they obtain funding. It also indicates the main source of revenues and changes that occurred during the existence of the Fund. The final part of the article deals with the impact of employment of convicts on the Fund and highlights its role as the main source of income. The issue of employment of convicts was developed and the functioning of the programme „Work for Prisoners” was basically described and analysed.
Keywords: post-penitentiary aid; released from prisons; employment of convicts; income above of the Fund; post-penitentiary assistance